In vitro cytotoxicity properties of Gnetum gnemon L. on selected cancer cell lines - Anka, Hadiza Abubakar (2014)
Most people dreaded the side effects of conventional cancer treatment and have resorted to alternative treatments such as herbal therapy which is often have less adverse side effects and less expensive. This study was conducted to evaluate the potential anticancer properties of Gnetum gnemon leave extracts on liver cancer (HepG2), colon adenocarcinoma (HT-29), hormone-dependent breast cancer (MCF-7) cell lines and normal mouse embryo fibroblast (3T3). MTT (3-(4,5-dimethylthiozol-2-yl)-2,5-diphenyltetrazolium bromide) assay, Acridine Orange/Propodium Iodide (AO/PI), Fourier Transform Infrared (FT-IR) and Gas chromatography-Mass Spectroscopy was analysed on both young and mature leave extracts of ethanol and hexane (YE, ME, YH and MH). All extracts inhibited proliferation of HepG2 in a concentration and time-dependent manner with high IC50 values 240.53, 138.53, 249.83 and 257.21 g/mL respectively. The outcome of the model used (fixed effect test) on the comparing parameters (maturity, solvent and time) on HepG2 cell lines, the young leaves showed a high significant difference (p<0.05) when compared to matured leaves. There was no significant difference between the two extraction solvents. On the other hand, time showed highly significant effect (p<0.001). All extracts was found to induce apoptosis at the IC50 concentrations in HepG2 due to presence of clear space, decrement in cell number, ooting cells and decrease in attached cell number after 72 hours. The AO/PI double staining of both treated and untreated HepG2 cells with IC50 concentations of YE and ME confirmed some apoptotic features such as membrane blebbing, cell size decreases and several necrotic cells after 72 hours. The FT-IR analysis of YE and ME showed several intense, sharp absorption peaks due to the different functional groups present (primary amines, secondary amines, alcohol, phenol, carboxylic acid, aromatics, esters, lactone, aldehyde and ketones). And the GC-MS analysis revealed important bioactive components such as squalene, α-tocopherol, α and β-sitosterol and Inositol in YE and phytol, inositol, β and ᶌ-sitosterol, α-tocopherol and phenol,2,4-bis(1,1-dimethyl) in ME. In summary, the morphological studies and AO/PI of treated HepG2 cells with both YE and ME for up to 72 hours incubation period showed some features of apoptosis. Conducting cytotoxicity assay with different extraction solvents is recommended.